ALIFE@Work: a randomised controlled trial of a distance counselling lifestyle programme for weight control among an overweight working population [ISRCTN04265725] - Hendriksen Ingrid JM; Dekkers Johanna C; Ariëns Geertje AM; van Wier Marieke F; Pronk Nico P; Smid Tjabe; van Mechelen Willem (BMC, 2006)
Abstract Background The prevalence of overweight is increasing and its consequences will cause a major public health burden in the near future. Cost-effective interventions for weight control among the general population are therefore needed. The ALIFE@Work study is investigating a novel lifestyle intervention, aimed at the working population, with individual counselling through either phone or e-mail. This article describes the design of the study and the participant flow up to and including randomisation. Methods/Design ALIFE@Work is a controlled trial, with randomisation to three arms: a control group, a phone based intervention group and an internet based intervention group. The intervention takes six months and is based on a cognitive behavioural approach, addressing physical activity and diet. It consists of 10 lessons with feedback from a personal counsellor, either by phone or e-mail, between each lesson. Lessons contain educational content combined with behaviour change strategies. Assignments in each lesson teach the participant to apply these strategies to every day life. The study population consists of employees from seven Dutch companies. The most important inclusion criteria are having a body mass index (BMI) ≥ 25 kg/m2 and being an employed adult. Primary outcomes of the study are body weight and BMI, diet and physical activity. Other outcomes are: perceived health; empowerment; stage of change and self-efficacy concerning weight control, physical activity and eating habits; work performance/productivity; waist circumference, sum of skin folds, blood pressure, total blood cholesterol level and aerobic fitness. A cost-utility- and a cost-effectiveness analysis will be performed as well. Physiological outcomes are measured at baseline and after six and 24 months. Other outcomes are measured by questionnaire at baseline and after six, 12, 18 and 24 months. Statistical analyses for short term (six month) results are performed with multiple linear regression. Analyses for long term (two year) results are performed with multiple longitudinal regression. Analyses for cost-effectiveness and cost-utility are done at one and two years, using bootstrapping techniques. Discussion ALIFE@Work will make a substantial contribution to the development of cost-effective weight control- and lifestyle interventions that are applicable to and attractive for the large population at risk.